2014
DOI: 10.1021/es504182e
|View full text |Cite
|
Sign up to set email alerts
|

Establishment, Characterization, and Toxicological Application of Loggerhead Sea Turtle (Caretta caretta) Primary Skin Fibroblast Cell Cultures

Abstract: Pollution is a well-known threat to sea turtles but its impact is poorly understood. In vitro toxicity testing presents a promising avenue to assess and monitor the effects of environmental pollutants in these animals within the legal constraints of their endangered status. Reptilian cell cultures are rare and, in sea turtles, largely derived from animals affected by tumors. Here we describe the full characterization of primary skin fibroblast cell cultures derived from biopsies of multiple healthy loggerhead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 64 publications
2
29
0
Order By: Relevance
“…The immunocytochemistry results in the present study showed the cells reacted strongly to the antibodies against vimentin, the specific marker for fibroblasts, while the cells reacted negative to the antibodies against cytokeratin, the epithelial marker, indicating PSF cells were fibroblastic. It was reported first as identification of fibroblast-like cells in P. sinensis and similar findings in a primary skin fibroblast cell of the sea turtle Caretta caretta have been described (Webb et al 2014). Isoenzyme analysis in this study revealed the PSF cell line had an LDH pattern of five bands and an MDH profile of two bands, which differs from other turtles or fish species.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The immunocytochemistry results in the present study showed the cells reacted strongly to the antibodies against vimentin, the specific marker for fibroblasts, while the cells reacted negative to the antibodies against cytokeratin, the epithelial marker, indicating PSF cells were fibroblastic. It was reported first as identification of fibroblast-like cells in P. sinensis and similar findings in a primary skin fibroblast cell of the sea turtle Caretta caretta have been described (Webb et al 2014). Isoenzyme analysis in this study revealed the PSF cell line had an LDH pattern of five bands and an MDH profile of two bands, which differs from other turtles or fish species.…”
Section: Discussionsupporting
confidence: 81%
“…Chromosome analysis, isoenzyme comparison, molecular biology, and immunohistochemistry techniques are commonly used for this purpose (Li et al 2009a, b;Freshney 2010;Wang et al 2013;Webb et al 2014). Karyotype analysis revealed a diploid chromosomal count of 2 N = 66 in majority of cells, which was identical to the modal chromosome number of PSF cell line; nevertheless, a variable karyotype formula was observed in P. sinensis cells because of the presence of sex chromosomes and the composition of sub-mediocentrics and relative small chromosome (Fu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in vitro, or cell-based, approaches have been used as an ethical alternative for assessing the effects of contaminants in sea turtles (e.g. Wang et al 2013b, Webb et al 2014, Wise et al 2014, Young et al 2015. Investigating toxicity thresholds for pollutants and the effects of complex chemical mixtures are important areas for future research.…”
Section: Q11 What Constitutes a Healthy Turtle?mentioning
confidence: 99%
“…The most common endpoint examined for in vitro exposure was cytotoxicity (n = 6), with 83% of these examining cytotoxicity of metals (Tan et al, 2010;Wang et al, 2013a;Wise et al, 2014;Young et al, 2015;Tong et al, 2016), and 17% examining organics (Webb et al, 2014). Two of these publications also examined genotoxicity (Wise et al, 2014;Young et al, 2015).…”
Section: Exposure Publications (In Vitro In Vivo)mentioning
confidence: 99%